Quaternary glaciolacustrine deposits around a Triple Junction site: Paleolakes at the foot of the Northern Patagonian Ice field (Argentina and Chile) - Isla, Federico Ignacio (2020)
The area involved by the triple junction between the South American, Nazca and Antarctic plates activity was affected by Quaternary glaciations. Before 12,800 yrs BP an extended ice field occupied the top of the Patagonian Andes, irradiating glaciers towards the east and the west dominantly. Towards the east, the ice melted in piedmont lakes; towards the west, fjords melted into the Pacific Ocean. The Upper-Pleistocene climate amelioration caused the recession of those glaciers. Some piedmont lakes reversed their Atlantic outflow towards to the Pacific Ocean. The glaciers retreat caused the fluvial reactivations along crustal former faults that were located below the ice. The Patagonian ice field became therefore split into present Northern and Southern fields. At the second largest lake of South America, the Buenos Aires-General Carrera Lake, the water level dropped from about 500 m over present mean sea level to 230 m. Several glaciolacustrine deposits from this area are indicating significant variations caused by climatic changes, volcanism and tectonics, differing in spatial and temporal magnitudes. The triple junction activity involved subduction of the Chile Ridge below the continental South American plate, volcanic activity and faulting. During the glacier melting the Baker River captured three eastern-moving glacial systems towards the southwest, towards the Pacific Ocean. This rapid event is thought to occur 12,800 yrs BP. The lowering of these glaciolacustrine systems should be also interpreted in terms of the tectonic activity in the region and considering other processes operating in the lakes and within the watersheds.